Education and Lifelong Learning as a Challenge for Silesia. Reflections on the Process of Regional Policy Governance for 2014–2020 Period - Ochojski, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Education can be seen as a strong condition for boosting the economy of a territory. More and more efforts have been recently made towards a governance-led process of formulating and implementing various levels of policy instruments. The new EU programming period has become an opportunity to test the governance issues and go through the multi-stakeholder and multi-territorial planning process for the benefit of education, i.e. one of the priorities in Silesia. The paper offers both methodological and empirical efforts to reflect upon the dialogue for a strong regional policy.